Mitochondrial complex I deficiency occurs in skeletal muscle of a subgroup of individuals with Parkinson’s disease - Simon Ulvenes Kverneng; Kjersti Eline Stige; Haakon Berven; Sepideh Mostafavi; Katarina Lundervold; Michele Brischigliaro; Brage Brakedal; Geir Olve Skeie; Irene Hana Flønes; Lilah Toker; Erika Fernandez-Vizarra; Ragnhild Eide Skogseth; et al. (Communications Medicine)
Abstract Background Widespread neuronal mitochondrial complex I (CI) deficiency was recently reported to be a characteristic in a subgroup of individuals with idiopathic Parkinson’s disease (PD). Here, we sought to determine whether a CI-deficient subgroup could be discerned using clinically accessible muscle biopsies. We further hypothesized that the inconsistency of previous findings of mitochondrial respiratory impairment in PD muscle may be due to interindividual variation, with respiratory deficiency only occurring in a subgroup of cases. Methods Using a cross-sectional design, vastus lateralis needle biopsies were collected from 83 individuals with PD and 29 neurologically healthy controls and analyzed by immunohistochemistry for CI and complex IV (CIV), cytochrome c oxidase/succinate dehydrogenase (COX/SDH) histochemistry, and spectrophotometric activity assays of complexes I–IV. Mitochondrial DNA (mtDNA) copy number, deletions, and point variation were analyzed in single muscle fibers and bulk biopsy samples. Results We show that PD muscle exhibits reduced CI activity at the group level, with 9% of cases falling below two standard deviations of the control group. In contrast, the activities of CII–CIV are not significantly different between the PD and control groups. No quantitative change of CI or CIV is detected, and the observed functional CI deficiency is not associated with mtDNA abnormalities. Conclusions Our findings support the existence of a PD subpopulation characterized by CI pathology in skeletal muscle and suggest that stratification by extra-neural mitochondrial dysfunction may be informative for selecting individuals for clinical trials.